Pneumococcal meningitis--comparison of therapy and vaccination costs - Madar, R; Malechova, L; Baska, T (Bratislavske lekarske listy, 2008)
The authors analysed the direct cost associated with treatment of IPI in 156 patients hospitalised with the diagnosis of pneumococcal meningitis at the terciary care Teaching Hospital. The total direct cost for 156 patients was 22,180,080 CZK (Czech Crowns). The average length of hospital stay for the patient with invasive pneumococcal meningitis (IPM) was 23 days. It was possible to conclude, that the direct financial expenses in 156 patients with pneumococcal meningitis would enable 88,337 people to be vaccinated. This is 6.2 % of all people in 65+ age group living in the Czech Republic, 54.8 % of all people in 65+ age group living in the Morava-Silesia Region with 1,250,800 inhabitants, or all inhabitants below 14 and above 65 years in Ostrava city (total population 312,000). The cost of pneumococcal polysacharide vaccine and its administration was 566 times lower compared to the average cost of treatment for one IPM case (Ref.21). Full Text (Free, PDF) www.bmj.sk.
Keywords: pneumokokové vakcíny; Health Care Costs; Aged; náklady na zdravotní péči; pneumokoková meningitida; Meningitis, Pneumococcal; vakcinace; Humans; Česká republika; Costs and Cost Analysis; senioři; lidé; Pneumococcal Vaccines; náklady a analýza nákladů; Czech Republic; Vaccination